2010
DOI: 10.1139/l10-077
|View full text |Cite
|
Sign up to set email alerts
|

Flexural behaviour of concrete beams strengthened with near surface mounted fibre reinforced polymer bars

Abstract: Fibre reinforced polymer (FRP) composite materials have been used as internal and external reinforcement for concrete structures. Flexural strengthening of concrete elements using near surface mounted (NSM)–FRP materials are a promising technology. This research is designed to investigate the behaviour of reinforced concrete beams strengthened in flexure with NSM–FRP bars. A total of 20 reinforced concrete beams were tested. Different parameters including internal steel reinforcement ratio, type of NSM–FRP bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 5 publications
0
44
0
Order By: Relevance
“…The results reported in [23] suggested that a bond length greater than 80 times the bar diameter had a significant effect on strengthening the NSM reinforcement. In contrast, according to the results stated in [24], there was only an insignificant increase in the load capacity of the beams strengthened with NSM bars when the bond length exceeded48 times the bar diameter.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The results reported in [23] suggested that a bond length greater than 80 times the bar diameter had a significant effect on strengthening the NSM reinforcement. In contrast, according to the results stated in [24], there was only an insignificant increase in the load capacity of the beams strengthened with NSM bars when the bond length exceeded48 times the bar diameter.…”
Section: Introductionmentioning
confidence: 83%
“…These have shown that the technique is greatly affected by bond behavior mainly depending on FRP properties, groove surface and dimensions, adhesive and concrete properties and the position of the FRP reinforcement. The technique has been used to increase the flexural and shear capacities of concrete members [1,[14][15][16][17][18][19][20][21][22][23][24]. In [22], the effect of filling material, concrete properties and bond length on the flexural behavior of RC beams strengthened by NSM reinforcement under a four-point load test was studied.…”
Section: Introductionmentioning
confidence: 99%
“…It is based on gluing FRP bars to the concrete near the external surfaces of the tensile zone by mounting the FRP bars in groves cut in the concrete surface [16,17]. Several experimental investigations have been reported on the bond behavior and flexural strengthening of concrete members with NSM FRP reinforcement [18][19][20][21][22][23][24][25][26][27][28][29]. Most of these studies have shown that the technique is greatly influenced by bond between FRP bars and concrete, mainly depending on FRP properties, groove surface and dimensions, adhesive and concrete properties and the position of the FRP reinforcement [21][22][23][24][25][26][27].…”
mentioning
confidence: 99%
“…Most of experimental study was conducted to investigate the flexural behavior of reinforced concrete beam with NSM-FRP bar (AlMahmoud, Castel, François, & Tourneur, 2009;Badawi & Soudki, 2009;De Lorenzis, Nanni, & Tegola, 2000;El-Hacha & Gaafar, 2011;El-Hacha & Rizkalla, 2004;Soliman, El-Salakawy, & Benmokrane, 2010) or strip (El-Hacha and Rizkalla, 2004). The test results confirm that NSM FRP rods can be used to significantly increase the flexural capacity of RC elements.…”
Section: State Of the Artmentioning
confidence: 99%